Aortic Hemodynamics with Accelerated Dual-Venc 4D Flow MRI in Type B Aortic Dissection - Kilinc, Ozden; Baraboo, Justin; Engel, Joshua; Giese, Daniel; Jin, Ning; Weiss, Elizabeth K.; Maroun, Anthony; Chow, Kelvin; Bi, Xiaoming; Davids, Rachel; Mehta, Christopher; Malaisrie, S. Chris; et al. (Applied Sciences, 2023)
The aim of this study is to investigate the applicability of the dual-venc (DV) 4D flow magnetic resonance imaging (MRI) to quantify the complex flow patterns in type B aortic dissection (TBAD). One GRAPPA-accelerated single-venc (SV) and one compressed-sensing (CS) accelerated DV 4D flow MRI sequences are used to scan all subjects, including twelve chronic TBAD patients and two volunteers. The scans are performed twice for the reproducibility assessment of the scan protocols. Voxelwise quantitative flow parameters including kinetic energy (KE), peak velocity (PV), forward and reverse flows (FF, RF) and stasis are calculated. High-venc (HV) data from the DV acquisition are separately analyzed. The scan time reduction by the CS-accelerated DV 4D flow MRI acquisition is 46.4% compared with the SV acquisition. The DV velocity-to-noise ratio (VNR) is higher compared with HV (p = 0.000). No true lumen (TL) parameter shows a significant difference among the acquisition types (p > 0.05). The false lumen (FL) RF is higher in SV compared with the DV acquisition (p = 0.009). The KE is higher (p = 0.038) and stasis is lower (p = 0.01) in HV compared with SV acquisition. All FL parameters except stasis are higher and stasis is lower in HV compared with DV acquisition (p < 0.05). Positive Pearson correlations among the acquisition types in TL and high agreements between the two scans for all acquisition types are observed except HV RF in the FL, which demonstrates a moderate agreement. The CS-accelerated DV 4D flow MRI may have utility in the clinical daily routine with shortened scan times and improved velocity measurements while providing high VNR in TBAD. The observed hemodynamic flow trends are similar between GRAPPA-accelerated SV and CS-accelerated DV 4D flow MRI acquisitions; however, parameters are more impacted by CS-accelerated HV protocol in FL, which may be secondary to the CS regularization effects.
CRIS-Team Scopus Importer:2023-07-07
Keywords: 4D flow MRI; aorta; dissection; flow; imaging; quantitative imaging; type B aortic dissection